Surface newt Calotriton asper acclimation to cave conditions improved their foraging ability in darkness - Guillaume, Olivier (Frontiers in Ecology and Evolution, 2022)
Caves in temperate regions are characterized by food scarcity compared to surface habitats. Therefore, hypotheses on adaptation to cave life suggest that many characteristics, such as resistance to starvation, reduced energy demand, and increased food-finding ability, have evolved among cave dwellers to cope with food frugality. To test the hypothesis involving increased food-finding ability, the prey detection performances of three surface and three subterranean populations of the Pyrenean newt, Calotriton asper, were compared. First, the rapidity of surface individuals in capturing prey at short distances inside a restricted aquarium under dark and light conditions and their score for capturing prey in a larger aquarium under similar conditions were measured. Simultaneously the scores obtained from individuals in cave populations in darkness were compared. Individuals from surface population 1 were maintained in darkness for approximately five years and retested. The surface C. asper individuals captured prey faster at short distances under light conditions than in total darkness; however, the differences were not significant. The scores of the surface C. asper individuals in the large aquarium were significantly better in darkness than in light conditions. In addition, the scores of cave populations at short distances in darkness were better than those of epigean populations in light conditions; however, in all cases, the differences were not significant. Finally, the scores of surface individuals maintained in darkness for five years improved. To explain these results, it should be noted that surface C. asper populations forage at night using non-visual cues (e.g., chemical and mechanical cues), further suggesting that vision may somewhat inhibit other senses. This ability to forage at night may be favorable for cave colonization. Moreover, some hypogean populations, when the use of prey-detecting non-visual senses has developed, may start to exhibit adaptivity.